INTERNATIONAL HARMONY AND RELIGIOUS TOLERANCE - Mallaeva Shohida Muqumjon qizi; Mamatov Mamadjon Akhmadjonovich (PEDAGOGS, 2023)
Abstract: The national idea has a wide content. It is shared with the ideals of interethnic harmony and national and religious tolerance. From this point of view, it can be said that the national ideal is the expression of the goals and interests of all the citizens of the country, regardless of nationality, race, and religious belief, who contribute valuable power to the development and prosperity of society, not just one nation. This article provides information about harmony and religious tolerance in interethnic relations.